Whole-farm nitrogen cycling and intensification of crop-livestock systems in the highlands of Madagascar: An application of network analysis - Álvarez, S.; Rufino, Mariana C.; Vayssières, Jean-François; Salgado, P.; Tittonell, Pablo A.; Tillard, E.; Bocquier, F. (Elsevier, 2014)
Food insecurity, soil fertility depletion and strong competition for biomass are commonly observed in smallholder crop-livestock systems. The objective of this study was to explore options to improve farm-level nitrogen cycling, productivity and economic performance through the analysis of N flows within four contrasting crop-livestock farm systems of Madagascar highlands. Farms were conceptualized as networks where the compartments were the household and their farming activities, all connected by N flows. Indicators assessing network size and cycling, and the organization and diversity of the N flows, were compared with system productivity, food self-sufficiency, and gross margins for the current situation and under four scenarios of intensification (i) dairy production increased by increasing N inputs as supplementary feed; (ii) crop production increased by increasing N inputs as mineral fertilizer; (iii) manure management improved to increase N conservation during storage and application to soils; (iv) a combination of the two most economically attractive scenarios (i and iii). The four case study farms represent local diversity differing widely in terms of network size, with total annual system N throughput ranging from 113 to 1037 kg N per capita, and in terms of N cycling, from 3 to 41 kg N per capita per year. They differed less in terms of external dependence, from 0.26 to 0.41 kg N kg N−1. Improving N conservation through improved manure management (scenario iii) had a positive impact on gross margin, and this in combination with increased concentrate supply (scenario iv) led to increases in whole-farm N use efficiencies from 2% to 50%, in N cycling from 9% to 68% and in food self-sufficiency from 12% to 37% across farm types. Gross margin was the most sensitive indicator to changes in management. Intensification through scenario iv had the highest impact on farm productivity, gross margin, food self-sufficiency, and environment sustainability (N use efficiency, capacity of the soil to stock N).